2018
DOI: 10.1111/jwas.12526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Novel Experimental Microdiet Types on Growth, Survival, and Pigmentation during the Weaning Period of the Fine Flounder, Paralichthys adspersus, Larvae

Abstract: The aim of this study was to evaluate two new types of experimental weaning microdiets for fish larvae, using the same formulation, but with different manufacturing processes, microextrusion marumerization (MEM) and particle‐assisted rotational agglomeration (PARA). Both microdiets were compared to a commercial microdiet, Otohime™ (OTO), during the weaning of the fine flounder, Paralichthys adspersus. Weaning was achieved by cofeeding with live food from 40 to 50 d after hatch (d.a.h.). Thereafter, only the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The buoyancy, sinking speed, and leaching losses of nutrients for all tested diets were not measured or compared during the feeding trial; however, the chemical attractiveness, physical characteristics, color, particle size, shape and manufacturing techniques, and nutrient leaching of diets in water could influence feed intake and nutrient utilization by pre‐ and post‐metamorphic stage fish (Lipscomb, Patterson, Wood, Watson, & DiMaggio, 2020; Teshima et al, 2000). Orihuela et al (2018) also found that the particle‐assisted rotational agglomeration (PARA) microdiets showed better performance for Fine flounder, Paralichthys adspersus as compared with Otohime diets because the manufacturing process produces less dense and smaller particle size PARA diets reducing sinking rates and increasing the probability of the larvae in detecting and ingesting the diet. We assume that our UNCW‐formulated diets were comparable or better than the other two commercial diets in terms of chemical attractiveness, buoyancy in water, and physical characteristics of the particles as evidenced by the higher growth performance of fish fed D1 and D2 diets.…”
Section: Discussionmentioning
confidence: 99%
“…The buoyancy, sinking speed, and leaching losses of nutrients for all tested diets were not measured or compared during the feeding trial; however, the chemical attractiveness, physical characteristics, color, particle size, shape and manufacturing techniques, and nutrient leaching of diets in water could influence feed intake and nutrient utilization by pre‐ and post‐metamorphic stage fish (Lipscomb, Patterson, Wood, Watson, & DiMaggio, 2020; Teshima et al, 2000). Orihuela et al (2018) also found that the particle‐assisted rotational agglomeration (PARA) microdiets showed better performance for Fine flounder, Paralichthys adspersus as compared with Otohime diets because the manufacturing process produces less dense and smaller particle size PARA diets reducing sinking rates and increasing the probability of the larvae in detecting and ingesting the diet. We assume that our UNCW‐formulated diets were comparable or better than the other two commercial diets in terms of chemical attractiveness, buoyancy in water, and physical characteristics of the particles as evidenced by the higher growth performance of fish fed D1 and D2 diets.…”
Section: Discussionmentioning
confidence: 99%
“…Larva survival and growth are affected by starter feed, which must satisfy nutritional needs immediately after depletion of the yolk sac (Puvanendran & Brown, 1999), and feed composition and feeding strategy are of critical importance (Lee, 2003). The timing of weaning is considered to be the most important factor in successful larva feeding in peled Coregonus peled (Gmelin) (Stejskal et al, 2017), pikeperch Sander lucioperca (L.) (Hamza, Mhetli, & Kestemont, 2007), totoaba Totoaba macdonaldi (Gilbert) (Mata‐Sotres, Lazo, & Baron‐Sevilla, 2015), burbot Lota lota (L.) (Palińska‐Żarska et al, 2014), golden pompano Trachinotus ovatus (L.) (Ma et al, 2015), fine flounder, Paralichthys adspersus (Orihuela et al, 2018), Japanese flounder, Paralichthys olivaceus (Geng et al, 2019), and butter catfish Ompok bimaculatus (Bloch) (Pradhan, Jena, Mitra, Sood, & Gisbert, 2014). The majority of these reports also described a positive effect of LF for initial feeding, and exclusive use of starter diets in early stages of rearing is often suggested to have negative effects on later development (Bochert et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding strategies can influence a range of physiological and production parameters (Geng et al, 2019; Lall, Lewis‐McCrea, & Tibbetts, 2018; Orihuela et al, 2018). Farmed fish may display considerable species‐specificity in feeding patterns.…”
Section: Introductionmentioning
confidence: 99%